Selectivity of enzymes involved in the formation of opposite enantiomeric series of p-menthane monoterpenoids in peppermint and Japanese catnip - Srividya, Narayanan (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2021 Elsevier B.V. All rights reserved.